(untitled) (International Journal of Food and Nutritional Sciences, 2022)
extreme discharge of sewage, drainage, domestic and other wastes flow of insecticides, pesticides with hazardous for aquatic animals. This politicians diamond the aquatic in ormond and cars depletion of dissolve oxygen of water bodies. Thus result in the increasement of BOD, COD, TS, TSS and pH of the water body. In the present research paper an attempt has been made to study the effects of different types of pollutants that are discharged in Nawatoli pond at different sites, on the growth of catla catla.